PERLINDUNGAN HUKUM TERHADAP OLAHRAGAWAN (KAJIAN PASAL 1365 KUHPERDATA DAN UNDANG-UNDANG NO 11 TAHUN 2022 TENTANG KEOLAHRAGAAN) - Dwisari, Amelia; Noer, Zakiah; Effendi, Prihatin (Judge : Jurnal Hukum, 2026)
This study analyzes the urgency of legal protection for athletes in Indonesia who frequently encounter risks of permanent injury, identity discrepancies, and economic exploitation without adequate compensation. Employing a normative legal research method with statutory and case approaches, this study examines the qualification of Tort (Perbuatan Melawan Hukum) under Article 1365 of the Indonesian Civil Code and its synchronization with Law Number 11 of 2022 concerning Sports. The results indicate that fulfilling the elements of a tort in a sporting context requires the integration of federations' reasonable care standards with the subjective rights of athletes. The synchronization of repressive-administrative and restorative-civil laws allows federative sanctions to be positioned as prima facie evidence to accelerate compensation claims while mitigating doctrinal hurdles such as volenti non fit injuria. The research recommends the formulation of derivative regulations regarding sport-specific safety standards, the utilization of the reversal of the burden of proof mechanism (omkering van het bewijslast), and the initiation of a National Sports Guarantee Fund to realize holistic and sustainable restitution for athletes' rights, in alignment with the vision of the Great Design of National Sports (DBON).